Nonalcoholic fatty liver disease alters microcystin-LR toxicokinetics and acute toxicity. (15th April 2019) - Clarke, John D.; Dzierlenga, Anika; Arman, Tarana; Toth, Erica; Li, Hui; Lynch, Katherine D.; Tian, Dan-Dan; Goedken, Michael; Paine, Mary F.; Cherrington, Nathan
Abstract: Microcystin-LR (MCLR) is a cyanotoxin produced by blue-green algae that causes liver and kidney toxicities. MCLR toxicity is dependent on cellular uptake through the organic anion transporting polypeptide (OATP) transporters. Nonalcoholic fatty liver disease (NAFLD) progresses through multiple stages, alters expression of hepatic OATPs, and is associated with chronic kidney disease. The purpose of this study was to determine whether NAFLD increases systemic exposure to MCLR and influences acute liver and kidney toxicities. Rats were fed a control diet or two dietary models of NAFLD; methionine and choline deficient (MCD) or high fat/high cholesterol (HFHC). Two studies were performed in these groups: 1) a single dose intravenous toxicokinetic study (20 μg/kg), and 2) a single dose intraperitoneal toxicity study (60 μg/kg). Compared to control rats, plasma MCLR area under the concentration-time curve (AUC) in MCD rats doubled, whereas biliary clearance (Clbil ) was unchanged; in contrast, plasma AUC in HFHC rats was unchanged, whereas Clbil approximately doubled. Less MCLR bound to PP2A was observed in the liver of MCD rats. This shift in exposure decreased the severity of liver pathology only in the MCD rats after a single toxic dose of MCLR (60 μg/kg). In contrast, the single toxic dose of MCLR increased hepatic inflammation, plasma cholesterol, proteinuria, and urinary KIM1 in HFHC rats more than MCLR exposed control rats. In conclusion, rodent models of NAFLD alter MCLR toxicokinetics and acute toxicity and may have implications for liver and kidney pathologies in NAFLD patients. Highlights: Systemic exposure to MCLR increased approximately two-fold in MCD-induced NAFLD. Biliary clearance of MCLR increased approximately two-fold in HFHC-induced NAFLD. MCD-induced NAFLD had the lowest hepatic MCLR levels and hepatic toxicity. HFHC-induced NAFLD exposed to MCLR had the highest plasma cholesterol, proteinuria, and urinary KIM1.